2017
DOI: 10.3390/biom7010006
|View full text |Cite
|
Sign up to set email alerts
|

Critical Minireview: The Fate of tRNACys during Oxidative Stress in Bacillus subtilis

Abstract: Oxidative stress occurs when cells are exposed to elevated levels of reactive oxygen species that can damage biological molecules. One bacterial response to oxidative stress involves disulfide bond formation either between protein thiols or between protein thiols and low-molecular-weight (LMW) thiols. Bacillithiol was recently identified as a major low-molecular-weight thiol in Bacillus subtilis and related Firmicutes. Four genes (bshA, bshB1, bshB2, and bshC) are involved in bacillithiol biosynthesis. The bsh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…As a result, our knowledge about the effects of tRNA modifications on codon-anticodon interactions, on maintenance of reading frame and on dynamics of tRNA on ribosome at high temperatures is limited. Furthermore, recent studies on mesophiles reported that tRNA modifications occur in response to environmental stresses or function as stress resistance factors ( Nawrot et al, 2011 ; Preston et al, 2013 ; Endres et al, 2015 ; Jaroensuk et al, 2016 ; Campos Guillen et al, 2017 ). As yet, however, there are no studies from this viewpoint for T. thermophilus .…”
Section: Perspectivementioning
confidence: 99%
“…As a result, our knowledge about the effects of tRNA modifications on codon-anticodon interactions, on maintenance of reading frame and on dynamics of tRNA on ribosome at high temperatures is limited. Furthermore, recent studies on mesophiles reported that tRNA modifications occur in response to environmental stresses or function as stress resistance factors ( Nawrot et al, 2011 ; Preston et al, 2013 ; Endres et al, 2015 ; Jaroensuk et al, 2016 ; Campos Guillen et al, 2017 ). As yet, however, there are no studies from this viewpoint for T. thermophilus .…”
Section: Perspectivementioning
confidence: 99%
“…Ginger root is rich with several potent antioxidant compounds such as gingerols, zingerone, zingiberene, glucosides-6-gingerdiol, flavonoids, and volatile oils [17]. These antioxidants protect both the reproductive organs from oxidative stress, an imbalance between prooxidants (reactive oxygen species such as superoxide ion, hydroxyl radical, and hydrogen peroxide) and antioxidants to the favor of the former [41], and lipid peroxidation. Ginger roots were found to enhance the activity of certain antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) in different male reproductive organs such as testis, prostate, and epididymis [32].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…It remains to be seen how these enzymes are affected under salt stress conditions during spore outgrowth, but Nagler et al (2016) reported the interesting observation that the cca gene was downregulated during 90 minutes of outgrowth in the presence of NaCl. A relevant feature is that the cca gene is immersed in the operon containing bacillithiol (a REDOX regulator and an α-anomeric glycoside of L-cysteinyl-D-glucosamine with L-malic acid) biosynthetic genes under σ A -dependent promoter control, which suggests that cca expression and the integrity of the 3’ terminus of tRNAs may be important during salt stress ( Campos Guillen et al , 2017 ; Gaballa et al , 2010 ; Gaballa et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%